(untitled) (GESTIÓN Y TENDENCIAS, 2020)
The voluntary savings pillar of the Chilean pension system offers three retirement savings options: Voluntary Pension Savings (APV), Collective Voluntary Pension Savings (APVC), and Agreed Deposits (DC). The purpose of these vehicles is to promote retirement saving so that people increase their future pensions and may eventually bring forward their retirement age. This article describes the structure of the voluntary retirement savings industry in Chile, presents some stylized facts about its development over the period 2003-2019, and sets out some challenges for its future growth.